A NOVEL FRAMEWORK FOR CONTINUOUS MONITORING OF SYSTEMS IN COMPUTER NETWORKS (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
This article aims to extend the lifetime of wireless instruments when some device lumps arerapidly closed under depressed conditions using the burden discovery approach retrievalprocess technique. The dispersion procedure techniques are included in the future retrievalprocedure, which is based on the organisation of inherited procedure. The techniquegenerates the required detecting knobs by substituting certain device knobs, and then certaindirection-finding routes are recycled. In our optional paper, the imitation procedure improvesthe dynamic knobs active towards a variety of 8.7 periods, and the recovery procedurereduces the volume of data damage by approximately 98.8%, and then reduces the frequencyof decrement alteration by closely active towards a variety of 31.1 percent.In the field of cyber-security, monitoring computer network traffic is a significant issue. Suchtraffic may be modelled as a data stream, which is a continuous succession of data pointswith uncertain dynamics. This study is about statistical anomaly detection on such streams,where the detector must run indefinitely without being supervised. We present a changedetection approach based on multivariate adaptive estimating in this so-called continuousmonitoring environment, which has the benefit of minimising the analyst's burden of settingcontrol parameter values. This technology is tested on genuine NETFLOW data taken fromthe Imperial College network and proved to be useful in simulated tests